2021
DOI: 10.3390/jcm10204787
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery and Surgical Volume-Specific Survival and Perioperative Outcome: Unmet Need for Evidence in Gynecologic Malignancy

Abstract: This study examined the effect of hospital surgical volume on oncologic outcomes in minimally invasive surgery (MIS) for gynecologic malignancies. The objectives were to assess survival outcomes related to hospital surgical volume and to evaluate perioperative outcomes and examine non-gynecologic malignancies. Literature available from the PubMed, Scopus, and the Cochrane Library databases were systematically reviewed. All surgical procedures including gynecologic surgery with hospital surgical volume informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Next, we reviewed the literature for similar cases. According to the 2020 edition of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement [ 21 ], we conducted a systematic literature search in the PubMed and Google scholar databases (first 100 hits) from their inception to 31 January 2022, as previously performed with modification [ 22 , 23 , 24 ]. The keywords “inguinal lymph node” or “groin lymph node” and “fallopian tube carcinoma,” “ovarian carcinoma,” or “primary peritoneal carcinoma” were used to search.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we reviewed the literature for similar cases. According to the 2020 edition of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement [ 21 ], we conducted a systematic literature search in the PubMed and Google scholar databases (first 100 hits) from their inception to 31 January 2022, as previously performed with modification [ 22 , 23 , 24 ]. The keywords “inguinal lymph node” or “groin lymph node” and “fallopian tube carcinoma,” “ovarian carcinoma,” or “primary peritoneal carcinoma” were used to search.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal management of ovarian metastasis after ovarian transposition in women with cervical cancer is understudied, including the feasibility of laparoscopic resection versus laparotomy. The Laparoscopic Approach to Cervical Cancer Trial for primarily treating early-stage cervical cancer, a prospective phase III randomized controlled trial, reported that minimally invasive surgery is correlated with worse disease-free and overall survival than open surgery [ 20 , 21 ]. Nevertheless, studies examining the safety and feasibility of laparoscopic resection for recurrent cervical cancer or ovarian metastasis are scanty [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%